Vitamin C and ubiquinone have the same ability in reducing the spermatozoa DNA fragmentation index in infertile men at Doctor Soetomo General Hospital, Surabaya, Indonesia - Ayang Halim; Supardi Supardi; Hamdani Lunardhi (DiscoverSys Inc., 2020)
Background: Infertility is one of the most common health problems in the world. Malefactors contribute to 50% of cases and about 15-30% of infertile men are categorized as unexplained infertility. There have been numerous studies investigating the role of spermatozoa DNA fragmentation in male infertility. Spermatozoa nuclear DNA integrity has been suggested as a better predictor of male infertility and oxidative stress has been known related to it. This study was conducted to determine the oral supplementation of Vitamin C and Ubiquinone in reducing the spermatozoa DNA fragmentation index (DFI) among infertile men. Methods: This was an experimental clinical trial with a pre-test and post-test group design. Thirty infertile men were randomized double-blindingly into 3 groups: Vitamin C and Ubiquinone; Vitamin C and Placebo; Ubiquinone and Placebo groups, each treatment was given for 35 days. The DFI was evaluated by Sperm Chromatin Dispersion (SCD) test, before and after treatment. Data were analyzed using SPSS version 21 for Windows.Results: The average age of respondents was 32.6 years old, followed by 4.6 years of infertility duration in 5.8 years of marriage. Most of the respondents had a normal Body Mass Index (BMI) (46.7%), no smoking history (75.0%), no history of heat (90.0%) or chemical (73.3%) exposure, and diagnosed with primary male infertility (90.0%). Vitamin C group showed a significant reduction in the spermatozoa DFI (95% CI, p<0.05), while the other two groups showed no differences in the spermatozoa DFIs (95% CI, p>0.05). Comparison analysis showed no differences in the reduction of the spermatozoa DFIs (95% CI, p>0.05) among these three groups. Conclusion: The recent findings suggest that oral supplementation of vitamin C can reduce the spermatozoa DFI, while ubiquinone and the combination of vitamin C and ubiquinone could not reduce the spermatozoa DFI.